PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU MEREK REEBOK (STUDI KASUS PADA MAHASISWA/I FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS WIJAYA KUSUMA SURABAYA) - Afrizal Rifqi Zaky Pramudya; Arochman, Maqbula (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Business competition in shoe products has experienced very rapid development in the current era, many shoe brand products have emerged and competed in the market. Reebok is one of the many brands used by consumers as one of their favorite shoe favorites. Therefore, this study is entitled "The Influence of Brand Image, Price, and Product Quality on Reebok Brand Shoe Purchase Decisions (Case Study on Students of the Faculty of Economics and Business, Wijaya Kusuma University, Surabaya). The approach used is a quantitative approach. The sample used in this study was purposive sampling with the criteria of active students of the Faculty of Economics and Business, Wijaya Kusuma University, and students who have used or bought Reebok shoes. The respondents needed in this study were 100 respondents who were samples processed by distributing online questionnaires via google form. The data was processed using IBM Statistic SPSS Version 22, with multiple linear regression analysis techniques. The results of this study indicate that Brand Image no significant , while Price and Product Quality have a significant effect on Reebok Brand Shoe Purchase Decisions.